?We Are from Nowhere?: A Qualitative Assessment of the Impact of Collective Trauma from the Perspective of Resettled Bhutanese Refugees (Mary Ann Liebert, 2021)
Background: Limited research has explored mental health concerns and collective trauma experienced by Bhutanese refugees due to their displacement from Bhutan, refugee camp life in Nepal, and resettlement to U.S. society. Purpose: To understand how collective trauma experienced by Bhutanese refugees influences the process of resettlement and integration into U.S. society to better address mental health concerns from the community. Methods: Qualitative data were collected through four focus groups (N=40) with Bhutanese refugee women in central Massachusetts from June to November of 2016 to discuss refugee resettlement experiences and mental health concerns. Findings: Bhutanese refugees shared insights on their resettlement experiences where several broader themes emerged, including historical collective trauma, closed-door culture, and processing mental health stigma. The displacement from Bhutan, hardships in Nepal refugee camps, and isolation in U.S. society led to a collective trauma among the community. Participants described America as having a closed-door culture that limits their integration into society, causing unique challenges based on their context of integration. The collective trauma also poses challenges toward processing mental health stigma, yet community building offers insights on how Bhutanese refugees can address these issues in collective spaces. Conclusions: The historical collective trauma must be considered when working with Bhutanese refugees to understand the context of their resettlement to address mental health concerns.